Cybersecurity Risks at Port - Tombak Mari-Liis; Zetterman Björn-Erik; Tapaninen Ulla Pirita (Transport and Telecommunication)
This paper focuses on assessing the cybersecurity risks associated with digital solutions used in ports. The assessment is conducted by using the European Union Agency for Cybersecurity (ENISA) guidelines for cybersecurity in the maritime sector in combination with guidance from the National Institute of Standards and Technology (NIST) and the ENISA Threat Landscape (ETL) report. As a result, the risk assessment considering the impact and the likelihood of cybersecurity risks occurrence was developed, followed by risk mitigation possibilities for ports. The novelty of this paper lies in its analysis of potential risks to ports, incorporating perspectives from different ports in the Baltic Sea region. During the assessment, the analysis revealed the highest threat event is ransomware, followed by moderate-level threats such as denial of service, malware, and threats to data. To effectively mitigate risks, ports should develop and test incident response plans, implement secure backup strategies, conduct regular staff training, and collaborate with partners.